Keefektifan Laboratorium Multimedia dalam meningkatkan specific lifeskill siswa SMK - Fikri Aulia; Wikan Budi Utami; S Suherman; Erwin Erlangga (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to analyze the relationship between students' perceptions of learning in the Multimedia Laboratory with two aspects of vocational students' specific life skills, namely academic skills and vocational skills. This research has a quantitative approach, with a correlational type. The research location is SMK Negeri 3 Tegal, with a population of 27 students of Class XI Multimedia Expertise Program. The population is also used as a sample. Data was collected using techniques and instruments in the form of observations, questionnaires and tests. The relationship between the independent variable and the dependent variable was analyzed using the Product Moment correlation technique. The results of the analysis reject the truth of the null hypothesis. At the 5% significance level, it was found that students' perceptions of learning in the Multimedia Laboratory were significantly related to students' academic skills (r 0,584); students' vocational skills (r 0.383); students' specific life skills (0,592).